Hadronic cross sections measurement with the SND detector at VEPP-2000 e+e− collider. (26th November 2015) - Achasov, M N; Barnyakov, A Yu; Barnyakov, M Yu; Beloborodov, K I; Berdyugin, A V; Berkaev, D E; Blinov, V E; Bobrovnikov, V S; Bogdanchikov, A G; Botov, A A; Buzykaev, A R; Dimova, T V; et al.
Abstract: The cross sections, , , , K + K −, , , have been measured with the spherical neutral detector at the VEPP-2000 e + e − collider in the energy range from 0.3 to 2.0 GeV.